EMOTION REGULATION, ACADEMIC STRESS, AND FINANCIAL STRESS AS PREDICTORS OF BURNOUT AMONG SOCIAL WORK STUDENTS AT DAVAO DEL NORTE STATE COLLEGE - Jerome Llevado; Rizalyn Febb Sarte; Zorich Shane Relatado; Mariamae Grengia (Journal of Social Work Education and Practice)
This study focuses on the predictors of burnout among social work students of Davao del Norte State College. It aims to determine whether emotion regulation, academic stress, and financial stress predict burnout. It employed a descriptive-predictive quantitative research design and utilized a survey questionnaire to gather data from respondents, specifically 287 second to fourth-year social work students enrolled on the 2nd semester of the academic year 2023-2024 at Davao del Norte State College, Panabo City. Multiple regression analysis was used to analyze the responses from the respondents. The results revealed that emotion regulation, academic stress, and financial stress are all substantial predictors of burnout F (3, 283) = 33.657, p <. 001. This indicates that if these predictors intensify and are not managed properly, there is a high possibility of burnout escalating that could also lead to problems in the general health of the students as well as their academic performance. The study highlights the need for institutional support, particularly from the school Guidance Office and Social Work faculty, to develop interventions that help students manage their emotions, academic stress, and financial challenges.